2020
DOI: 10.1038/s41393-020-0495-6
|View full text |Cite
|
Sign up to set email alerts
|

Understanding how a community-based intervention for people with spinal cord injury in Bangladesh was delivered as part of a randomised controlled trial: a process evaluation

Abstract: Design Mixed methods study Setting Community, Bangladesh Objectives To understand how a community-based intervention for people with spinal cord injury (SCI) in Bangladesh was delivered as part of a randomised controlled trial and to gauge the perceptions of participants and healthcare professionals to the intervention. Methods A community-based intervention was administered to 204 participants as part of a large randomised controlled trial (called the CIVIC trial). Case-managers followed-up participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Economic vulnerability and the impact on disability and health outcomes must be considered when developing prevention interventions. [37,38] The most prevalent SHCs were pain (78.1%), bladder problems (64.8%) and bowel problems (53.8%). Pain and bladder and bowel problems are the most commonly reported and significant SHCs experienced by people with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Economic vulnerability and the impact on disability and health outcomes must be considered when developing prevention interventions. [37,38] The most prevalent SHCs were pain (78.1%), bladder problems (64.8%) and bowel problems (53.8%). Pain and bladder and bowel problems are the most commonly reported and significant SHCs experienced by people with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…If there was any evidence of a complication, the healthcare professional provided advice to the participant and the participant's family about management of the complication and then more closely monitored the participant until the complication had resolved. Where necessary and possible, the healthcare professionals referred participants to local service providers (although our process evaluation indicated that these services were either not available or difficult to access [18]). The advice provided to participants followed international clinical practice guidelines [19][20][21] modified for the Bangladesh context.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were also provided with health care products such as wound dressings and urinary catheters to a total of AUD80 (~USD51) if they could not otherwise afford these items (see ref. [18] for more details).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these is to bring the treatment strategies into the home or community of people living with stroke; this is known as community-based intervention (CBI). CBI is delivered either to a set place within the community or at the residences of people with disability, with a single person or a group receiving the service at a time (Iemmi et al, 2015;Liu et al, 2020;Ryan, Enderby, & Rigby, 2006). CBI has been developed in both LMICs and HICs to provide people living with stroke continued rehabilitation services after discharge from hospital care, to augment limited healthcare services, and to promote strategies for the prevention of certain conditions (Iemmi et al, 2015;Johnson, Bird, Muthalib, & Teo, 2020;Magwood et al, 2020;Mannan et al, 2012;Yan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%